FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN SERTA DAMPAKNYA TERHADAP MINAT BELI ULANG KONSUMEN (STUDI PADA BLENDS PASTA & CHOCOLATE CABANG UNIKA SEMARANG) - Putri, Anindya Dwiana; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2017)
Culinary businesses are keep booming and growing nowadays, which causing a tighter competition between all culinary businesses’ owners. The main purpose of this research is to get to know if there’s any impact of product quality, service quality and customer value on customer repurchase intention at Blends Pasta & Chocolate Unika Semarang with customer satisfaction as the intervening variable.A total sample of 100 respondents are taken by purposive sampling technique and all obtained from Blends Pasta & Chocolate’s Unika Semarang customers who purchased at least 2 times before. All data are collected from both opened and closed questions on questioner’s answer. The method for analyzing data is using double regression method on SPSS 21 version.The result from data analysis showed that product quality, service quality, and customer value variables have all positive and significant impact toward customer satisfaction with coefficient regression Y1=0,354X1 + 0,276X2 + 0,275X3. Meanwhile costumer satisfaction’s variable has positive and significant impacts toward customer repurchase intention variable with coefficient regression Y2 = 0,747Y1.